The Role Of Muslim Entrepreneurs In The Coal Weaving Industry During Pandemic Based On Local Wisdom - Hasan Sazali; Rizal Agus; OK Bilqis Amini (ITB AAS INDONESIA Surakarta, 2022)
The Role of Muslim Entrepreneurs in the Coal Weaving Industry Based on Local Wisdom shows that the role of Muslim entrepreneurs has contributed to the surrounding community as evidenced by the increasing number of workers or weaving craftsmen, where in the past the community was known as the lazy Malay myth which is a construction of negative cultural habits attach)ed to Malay self. Then the increase in weaving production innovations that not only manages songket weaving into clothing but also combines songket into several variations such as bags, pillowcases, wallets, sandals, caps, tanjak, and shoes, this is also evidence that there is a link between the construction of cultural values and An artifact that has become the local wisdom of the Malays is songket cloth. It is also proven by packaging innovations that are designed to be as attractive as possible with their respective business brand names. This is also inseparable from the support of the Batu Bara district government which provides assistance in the form of looms and provides a forum for entrepreneurs to beautify their sales packaging by constructing a building called a packaging house that can be used by entrepreneurs to develop their businesses so that they are competitive.